Open Government Index in Local Government During the Period of the COVID-19 Pandemic - Tiara Khairunnisa; Achmad Nurmandi; Titin Purwaningsi; Mohammad Jafar Loilatu; Annisa Ghina Savira (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
Identification that has been carried out in studies of open data government and e-government has been widely described from various perspectives. This study aims to examine how the government applies open government data. This study analyzed the existing open government of local government in Indonesia during the COVID-19 period, providing information to test the transparency of existing local governments. This study adopts the Benchmark Model Evaluating Data Openness theory and E-Gov assessment using a quantitative approach by dividing several categories and assessment variables. The open government analysis assessment uses a score of 1-5, and a web assessment with a score of 100. From this calculation, it is found that the five provinces with increased cases have high OGD scores. The results are plotted based on the spread of COVID-19 throughout Indonesia, as determined by reviewing and surveying the provincial government's COVID-19 website. West Java (89.87), East Java (89.87), Jakarta (88.75), Central Java (88.37), and Yogyakarta (88.37) all had high and nearly balanced total scores (84.87). The increased assessment results are supported by infrastructure and good management, and the five areas are